(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
This study focuses on the annual updating of the state scale series topographic maps of the Republic of Armenia using high-resolution satellite imagery for photogrammetric processing. It outlines methods for creating planimetric and elevation reference points for ground control, ensuring their alignment with the National Geodetic System of Armenia. The research explores various geodetic techniques, including satellite-based positioning, second-order polygonometry, high-precision theodolite traverses, and trigonometric leveling for elevation determination. The accuracy of coordinate and elevation measurements obtained through these methods is assessed. Additionally, a standardized data processing format for control points is proposed to streamline and enhance the efficiency of office-based photogrammetric work. A list of materials that must be submitted upon completion of the work is provided.